Positive Selection of Squalene Synthase in Cucurbitaceae Plants. (9th May 2019) - Qian, Jieying; Liu, Yong; Ma, Chengtong; Chao, Naixia; Chen, Qicong; Zhang, Yangmei; Luo, Yu; Cai, Danzhao; Wu, Yaosheng
Abstract : Triterpenoid saponins are secondary metabolites synthesized through isoprenoid pathways in plants. Cucurbitaceae represent an important plant family in which many species contain cucurbitacins as secondary metabolites synthesized through isoprenoid and triterpenoid pathways. Squalene synthase ( SQS ) is required for the biosynthesis of isoprenoids, but the forces driving the evolution of SQS remain undetermined. In this study, 10 SQS cDNA sequences cloned from 10 species of Cucurbitaceae and 49 sequences of SQS downloaded from GenBank and UniProt databases were analyzed in a phylogenetic framework to identify the evolutionary forces for functional divergence. Through phylogenetic construction and positive selection analysis, we found that SQS sequences are under positive selection. The sites of positive selection map to functional and transmembrane domains. 180L, 189S, 194S, 196S, 265I, 289P, 389P, 390T, 407S, 408A, 410R, and 414N were identified as sites of positive selection that are important during terpenoid synthesis and map to transmembrane domains. 196S and 407S are phosphorylated and influence SQS catalysis and triterpenoid accumulation. These results reveal that positive selection is an important evolutionary force for SQS in plants. This provides new information into the molecular evolution of SQS within the Cucurbitaceae family.